Crowdfunding webcomics: the role of incentives and reciprocity in monetising free content - Dowthwaite, Liz (2018)
The recent phenomenon of internet-based crowdfunding has enabled the creators of new products and media to share and finance their work via networks of fans and similarly-minded people instead of having to rely on established corporate intermediaries and traditional business models. This thesis examines how the creators of free content, specifically webcomics, are able to monetise their work and find financial success through crowdfunding and what factors, social and psychological, support this process. Consistent with crowdfunding being both a large-scale social process yet based on the interactions of individuals (albeit en mass), this topic was explored at both micro- and macro-level combining methods from individual interviews through to mass scraping of data and large-scale questionnaires.